Tournemire argillite/carbon steel evolution under bacterial influence after 10 years of in situ interaction. (September 2014) - Urios, L.; Maillet, A.; Dauzères, A.; Flachet, M.; Magot, M.
<x content-type="archive" xml:space="preserve">Abstract</x> The purpose of the present study was to characterise the physicochemical evolution of argillite/carbon steel coupons after 10 years of interaction inside the Tournemire Underground Research Laboratory (France). Carbon steel coupons were introduced in boreholes drilled in the geological formation in contact with the argillite, and were overcored 10 years later to study the interfaces. The iron release by steel corrosion induced mineralogical dissolutions (Ca phases) and precipitations (iron oxides and hydroxides), leading to a partial clogging of the argillite porosity. A sulphur enrichment was observed in the corrosion area, linked to a potential microbial activity. The biodiversities differed depending on the steel type, indicating the influence of iron–clay interactions. This analysis has shown the presence of bacteria known for their involvement in corrosion processes and isolates able to develop at elevated temperatures.